An economic analysis of biochar production using residues from Eucalypt plantations. (October 2015) - Wrobel-Tobiszewska, A.; Boersma, M.; Sargison, J.; Adams, P.; Jarick, S.
Abstract: Producing biochar from organic residues is a potential method to integrate carbon sequestration and residue management costs while enhancing conventional agricultural and forestry production systems. Plantation forestry is an important industry in Tasmania, and is based on large scale plantations of Pinus radiata and Eucalyptus ( Eucalyptus globulus and E. nitens ). The area covered by forestry plantations in Tasmania (on State land) exceeds 100 000 ha, while plantations on private land double this number. Eucalypt plantations are managed primarily for the production of high-value pruned logs for industry; however, unpruned saw logs, peelers, poles, posts and pulp are also produced, and significant quantities of residue are produced as a byproduct. This study was an economic analysis that considered on-site biochar production system using post-harvest forestry residues, with biochar being utilized within the system, or sold as a product. The financial analysis was based on previous experimental outcomes on the use of Macadamia shell biochar in Eucalyptus nitens plantations, and the local operating environment in Tasmania; including current forestry procedures used for managing plantations. A number of assumptions were considered concerning a) production costs, b) savings enjoyed by traditional operations, following biochar scenario implementation, and c) biochar sales. The analysis revealed a potential annual income of over 179 k (2014 value) and the sensitivity analysis identified the crucial factors responsible for scenario profitability, namely biochar price and final product distribution. Highlights: Eucalypt biochar production financial feasibility in Tasmania is investigated. Case study based on E. nitens forestry plantation agronomic and socio-economic results. Post-harvest residues used to make biochar on-site in a mobile pyrolyzer. Cost-benefit model reveals a potential for introducing scenario on a commercial scale. Biochar price and amount of material processed are crucial for financial feasibility.